Diseño de una red satelital de telecomunicaciones con tecnología vsat para la parroquia Columbe del cantón Colta - Yandun Espinosa, Robert Mikel (2024)
This project proposes the design of a satellite telecommunications network using VSAT technology as an alternative solution to provide internet access in remote areas without coverage from conventional telecommunications networks, such as the Columbe parish in the Colta canton. A point-to-multipoint network configuration in the Ku band has been selected, optimized to reduce costs and ensure stability in the face of adverse weather conditions. A detailed description of the elements (IDU, ODU) that make up the VSAT network is included, covering architectures, frequency bands, multiple access protocols, and their current applications. The characteristics, advantages, and disadvantages of satellite communications and the components of the VSAT system are also analyzed. A mathematical analysis of the radiofrequency link between the satellite and the ground station is conducted, taking into account the main parameters (atmospheric losses, rain effects, tracking losses, antenna gain, carrier-to-noise ratio, and bit energy-to-noise density ratio) that influence the network's performance. The process for calculating the required bandwidth for a VSAT satellite network is detailed, using Matlab's "Satellite Communications Toolbox" and "Satellite Link Budget Analyzer" tools to validate the calculations of the uplink and downlink power budget. This analysis is essential to demonstrate that the design meets the quality-of- service requirements in terms of upload and download speed, latency, error rate, and stability, ensuring a reliable connection for the community. The results obtained from simulations conducted in Matlab and GNS3 validated the design, optimizing key parameters such as the carrier-to-noise ratio (C/N) and bit energy-to-noise density ratio (Eb/No). This ensures good network performance, with significant improvements in upload speed (43.16%), download speed (45.28%), latency (21.76%), and a reduction in the error rate (21.19%) compared to the current connection available in Columbe.